Avaliação do nível de inovação tecnológica: desenvolvimento e teste de uma metodologia - Silva, Fábio Gomes da (2006)
The main objective of this research was to develop and test a methodology that makes possible to evaluate the level of technological innovation in organizations. The study was carried out through field research in 5 (five) manufacturing industries which are amongst the biggest, regarding profits, in the city of Ponta Grossa, State of Paraná, according to data available at the regional branch of the Paraná Industries Federation (FIEP) . The results of this research showed that it is possible to evaluate the level of technological innovation in companies through the methodology developed. Further results also pointed out that the most innovative companies are the ones that present highest profitability.